Oracle database 11g [ the complete reference - Loney, Kevin (McGraw-Hill, 2009)
"Oracle Database 11g: The Complete Reference explains how to use all the new features and tools, execute powerful SQL queries, construct PL/SQL and SQL*Plus statements, and work with large objects and object-relational databases. Learn how to implement the latest security measures, tune database performance, and deploy grid computing techniques. An invaluable cross-referenced appendix containing Oracle commands, keywords, features, and functions is also included."